2012
DOI: 10.3810/psm.2012.05.1966
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of Tommy John Surgery

Abstract: This study is the first of its kind to investigate public perception of Tommy John surgery and has identified an alarming percent of players, coaches, and parents with misperceptions. Efforts should be made in our communities to better educate players, coaches, and parents regarding elbow ulnar collateral ligament injury in youth baseball players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 18 publications
0
64
0
Order By: Relevance
“…High rates of misperception among young players, coaches, and parents have been identified regarding the risks, benefits, indications, and recovery associated with an MCL reconstruction surgery. 17 The initial management of MCL injury consists of rest, cold therapy, anti-inflammatory medications, and, occasionally, bracing. 18 Corticosteroid injections are not used owing to the detrimental effects on tissue integrity.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…High rates of misperception among young players, coaches, and parents have been identified regarding the risks, benefits, indications, and recovery associated with an MCL reconstruction surgery. 17 The initial management of MCL injury consists of rest, cold therapy, anti-inflammatory medications, and, occasionally, bracing. 18 Corticosteroid injections are not used owing to the detrimental effects on tissue integrity.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…Ahmad et al 65 noticed the increasing number of uninjured young throwers who presented at their clinic for medical evaluation, seeking UCL reconstructive surgery, and hypothesised that the general public has misguided perceptions regarding the causes of UCL injury and the indications, operative technique, risks, benefits and required rehabilitation. They found that over 25% of baseball coaches, players and parents do not believe that pitch count is a risk factor for elbow injury 65. In the same study, and arguably most importantly, 30% of baseball coaches, 37% of parents, 51% of high school athletes and 26% of collegiate athletes believed that UCL reconstruction in athletes without elbow injury would improve performance (figure 5).…”
Section: Considerationmentioning
confidence: 99%
“…A growing body of literature supports that paediatric elbow injury is correlated to increased baseball pitch counts in a game 4 11–13. Despite this awareness, a large percentage of coaches, players and parents continue to disregard pitch count and type of pitches as a risk factor for elbow injuries 14. Furthermore, there is the perception that medial collateral ligament (MCL) reconstruction is a viable prophylactic option for elbow injuries in overhead throwing athletes 14.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this awareness, a large percentage of coaches, players and parents continue to disregard pitch count and type of pitches as a risk factor for elbow injuries 14. Furthermore, there is the perception that medial collateral ligament (MCL) reconstruction is a viable prophylactic option for elbow injuries in overhead throwing athletes 14. These findings highlight confusion regarding orthopaedic treatment recommendations and a lack of consensus on the treatment options and outcomes of elbow injuries in young throwing athletes.…”
Section: Introductionmentioning
confidence: 99%